2003
DOI: 10.2298/jmmb0302209s
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Mg-Nd alloy obtained by electrolysis in molten oxifluoride media

Abstract: Mg-Nd alloys have been produced by electrolysis of the molten mixture LiF-NdF3-MgF2 using Nd2(CO3)3 and MgF2 as raw materials. An electrolysis cell was designed having the anode made of super dense graphite and the cathode made of molybdenum metal. The quasi-binary system (NdF3-LiF)eutectic-MgF2 was investigated and the liquidus line was determined using thermo-differential analysis. The solubility of Nd2(CO3)3 in the LiF-NdF3-MgF2 system was investigated by the carbothermal technique

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Yang et al [74] used NdF 3 -LiF-BaF 2 -Na 3 AlF 6 electrolyte and neodymium oxide and magnesium powder as electrolyte raw materials and obtained a uniform Mg-Nd master alloy with current efficiency of 72.6% by non-co-electrodeposition at 1323 K and a cathode current density of 6-7 A/cm 2 . V. Soare et.al [75,76] also adopted the liquid magnesium cathode deposition method, using 28.60 wt.% LiF-64.72 wt.% NdF 3 -6.68 wt.% MgF 2 as the electrolyte and Nd 2 (CO 3 ) 3 and MgF 2 as the electrolysis materials. Under the conditions of an electrolysis temperature of 1123 K and anodic and cathodic current densities of 3.9 A/cm 2 and 0.3 A/cm 2 , respectively, the current efficiency reached 87% and the rare earth recovery reached 83.17%.…”
Section: Re-mg Alloysmentioning
confidence: 99%
“…Yang et al [74] used NdF 3 -LiF-BaF 2 -Na 3 AlF 6 electrolyte and neodymium oxide and magnesium powder as electrolyte raw materials and obtained a uniform Mg-Nd master alloy with current efficiency of 72.6% by non-co-electrodeposition at 1323 K and a cathode current density of 6-7 A/cm 2 . V. Soare et.al [75,76] also adopted the liquid magnesium cathode deposition method, using 28.60 wt.% LiF-64.72 wt.% NdF 3 -6.68 wt.% MgF 2 as the electrolyte and Nd 2 (CO 3 ) 3 and MgF 2 as the electrolysis materials. Under the conditions of an electrolysis temperature of 1123 K and anodic and cathodic current densities of 3.9 A/cm 2 and 0.3 A/cm 2 , respectively, the current efficiency reached 87% and the rare earth recovery reached 83.17%.…”
Section: Re-mg Alloysmentioning
confidence: 99%
“…In the recent past, electrochemical co-deposition technique in molten salt media has been studied by researchers (Iida et al 2003; Schwartz et al 2004; Wang et al 2008; Groult et al 2010) for the production of RE based alloys to overcome the limitations of vacuum melting route. Several investigators have also reported the successful preparation of RE-Mg alloys employing molten salt electro-reduction technique (Soare et al 2003; Sahoo et al 2014b; Shidong et al 2015). Molten salt electrolysis offers advantages over vacuum melting process in terms of batch size, homogeneity of alloy composition, cost of production and simplicity in technology.…”
Section: Introductionmentioning
confidence: 99%
“…Electroplating techniques of REM and foundry alloy production are based on the electrolysis of fluorides, oxides or the mixture of fluorides and chlorides of alkali and earth metals in molten salts. At the same time, a carbon anode and an iron cathode are generally used when the electrolysis of neodymium fluoride or neodymium oxide is taking place [3][4][5][6][7]. The process is conducted at 650-1100 °С.…”
Section: Introductionmentioning
confidence: 99%